ANALYSIS OF PRODUCT QUALITY, SALES PROMOTION, BRAND IMAGES, AND AFTER-SALES SERVICE TOWARDS SAMSUNG GADGET PURCHASE DECISIONS - Lina Safitriani; I Gedhe Arimbawa; Agus Baktiono; Elok Damayanti (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2019)
This study aims to determine the effect of simultaneous and partial product quality, brand image, sales promotion and after-sales service on purchasing decisions of Samsung smartphones at the Discovery Mobile Store in Sidoarjo. This research used quantitative method. The population and sample based on the questionnaire distribution to consumers who visited the Discovery Ponsel Store Sidoarjo, and were taken as 135 respondents. Data collection techniques used interviews, observation and questionnaires. The data analysis used reliability test, validity test, classic assumption test and multiple linear analysis test. The simultaneous and partial results of product quality, brand image, sales promotion and after-sales service have a significant effect on the purchase decision of Samsung smartphones at the Discovery Ponsel Sidoarjo Store because of the significance of <0.005.